2023
DOI: 10.1038/s42003-023-05384-y
|View full text |Cite
|
Sign up to set email alerts
|

Origin of breath isoprene in humans is revealed via multi-omic investigations

Pritam Sukul,
Anna Richter,
Christian Junghanss
et al.

Abstract: Plants, animals and humans metabolically produce volatile isoprene (C5H8). Humans continuously exhale isoprene and exhaled concentrations differ under various physio-metabolic and pathophysiological conditions. Yet unknown metabolic origin hinders isoprene to reach clinical practice as a biomarker. Screening 2000 individuals from consecutive mass-spectrometric studies, we herein identify five healthy German adults without exhaled isoprene. Whole exome sequencing in these adults reveals only one shared homozygo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Fortunately, such an investigation was recently undertaken. In a multi-omic study of genes and metabolites, involving long-term isoprene measurements of the exhaled breath of thousands of people, Sukul et al have provided the definitive and conclusive proof of the proposition that isoprene production occurs in skeletal muscle cells [26]. In this remarkable study, Sukul et al identified an IDI2 stop-gain mutation as the cause for the absence of isoprene in the exhaled breath of five healthy individuals from the screening of the thousands of people.…”
Section: A Lack Of Isoprene-a Key To Unravel the Origin Of Human Isop...mentioning
confidence: 99%
“…Fortunately, such an investigation was recently undertaken. In a multi-omic study of genes and metabolites, involving long-term isoprene measurements of the exhaled breath of thousands of people, Sukul et al have provided the definitive and conclusive proof of the proposition that isoprene production occurs in skeletal muscle cells [26]. In this remarkable study, Sukul et al identified an IDI2 stop-gain mutation as the cause for the absence of isoprene in the exhaled breath of five healthy individuals from the screening of the thousands of people.…”
Section: A Lack Of Isoprene-a Key To Unravel the Origin Of Human Isop...mentioning
confidence: 99%
“…Similarly, in IMS, the retention time is plotted against the sum of the data points in the ion mobility spectrum in the range of 4.9 ms-11.0 ms without considering reactant ions. Therefore, the ketone mixture was measured at different APC pressures (40,50,60,70,80,90, and 100 kPa). The results can be seen in figure 6, upper part for MS and lower part for IMS.…”
Section: Coefficient Of Variation Of the Reproducibility Experiments Inmentioning
confidence: 99%
“…Isoprene is one of the most studied volatile compound in respiratory research, not only because it is the primary endogenous hydrocarbon found in exhaled human breath but also because of its potential use as a noninvasive marker for studying various metabolic processes in the body. Its origin was uncertain until now, but Sukul et al [40] have discovered the actual origin of human exhaled isoprene by multi-omic analysis of genes and metabolites. Exhaled 2-propanol in human breath reflects health conditions: There is a relationship with 2-propanol blood concentration and diabetes, so a link of its concentration in the breath can also be suspected [41].…”
Section: Application Example-breath Analysismentioning
confidence: 99%
“…For basic and applied breathomics (e.g., of unidentified VOC marker profiles) established gold standards like Gas-Chromatography Mass-Spectrometry (GC-MS) and real-time Proton-Transfer-Reaction Time-of-Flight Mass-Spectrometry (PTR-TOF-MS) represent the state of the art. As soon as certain markers are well-established as for breath isoprene [15] or acetone, PAS offers a compelling evidence of performance to comprehend potential pre-clinical point-of-care applications.…”
Section: Introductionmentioning
confidence: 99%